NOTES ON THE FLORA OF JAVA-VII* - A. G. L. ADELBERT (REINWARDTIA, 1954)
In connexion with Backer's "Beknopte Flora van Java," a revised key to, and short descriptions of, the species of Baccaurea Lour.(Euphorbiaceae) are given; the name Lannea coromandelica (Houtt.) Merr. is accepted; and three new species of Labiatae are validly published and described, viz., Pogostemon javanicus Backer ex Adelb., P. hortensis Backer ex Adelb.,and Plectranthus petraeus Backer ex Adelb.